Solidaritas Sosial Komunitas Chelsea Indonesia Supporters Club Pekanbaru - Nasution, Dzaky Amanda; Susanti, Rina (Peneliti.net, 2025)
The Chelsea Indonesia Supporters Club (CISC) Pekanbaru is a football fan community supporting Chelsea FC, based in Pekanbaru. This study aims to identify the forms of social solidarity within the community and describe the efforts to maintain solidarity among its members. The research employs Emile Durkheim's theory of social solidarity, which divides solidarity into mechanical and organic types. A qualitative descriptive method is applied, utilizing in-depth interviews, observations, and documentation as data collection techniques. The study subjects include six community members, with the regional coordinator serving as the key informant. The findings reveal the presence of mechanical solidarity, reflected in collective activities such as watch parties, futsal games, social actions, and other regular events. This solidarity is supported by factors such as camaraderie, a shared sense of purpose, and frequent interactions among members. Furthermore, organic solidarity is evident in the clear division of responsibilities within the community's organizational structure. The community successfully integrates elements of mechanical and organic solidarity, fostering a strong sense of togetherness among its members while maintaining the community's existence in supporting Chelsea FC. Keywords: Chelsea, Community, Football, Solidarity, Togetherness